2005
DOI: 10.1158/1055-9965.epi-04-0746
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms with Serum Estrogens Measured Multiple Times During a 2-Year Period in Premenopausal Women

Abstract: There is evidence that circulating estrogens are associated with breast cancer risk. In this study of premenopausal women, we explored the association of polymorphisms in genes in the estrogen synthesis and metabolism pathways with serum and urinary levels of estrone (E 1 ) and estradiol (E 2 ) and with the urinary ratio of 2-hydroxyestrone (2-OHE 1 )/ 16A-hydroxyestrone (16A-OHE 1 ). This analysis included 220 women, who were participants in a 2-year randomized soy intervention. Blood specimens were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
6
33
1
Order By: Relevance
“…Current data regarding the effects of genotype on hormone levels, however, are limited. Consistent with previous reports, we showed no difference in estradiol levels with a polymorphism in CYPc17α [12] and no difference in estradiol or estrone levels with a polymorphism in COMT [16,40], CYP19 [40], or CYP1B1 [40]. Other studies, however, have shown lower estradiol [10,11] and estrone [10] levels with a polymorphism in CYP19.…”
Section: Discussionsupporting
confidence: 92%
“…Current data regarding the effects of genotype on hormone levels, however, are limited. Consistent with previous reports, we showed no difference in estradiol levels with a polymorphism in CYPc17α [12] and no difference in estradiol or estrone levels with a polymorphism in COMT [16,40], CYP19 [40], or CYP1B1 [40]. Other studies, however, have shown lower estradiol [10,11] and estrone [10] levels with a polymorphism in CYP19.…”
Section: Discussionsupporting
confidence: 92%
“…Our results for CYP17 add to the growing number of studies reporting little or no association for genetic control by this particular SNP and hormone levels [18,19,[30][31][32][33][34][35][36]. Similarly, there is little evidence that circulating hormone levels vary substantially by the CYP1B1 or COMT genotypes [18,19,35,36]; however, the relationship with urinary metabolites of estrogen has been more consistent with higher concentrations observed for the variant genotypes [19,37].…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, there is little evidence that circulating hormone levels vary substantially by the CYP1B1 or COMT genotypes [18,19,35,36]; however, the relationship with urinary metabolites of estrogen has been more consistent with higher concentrations observed for the variant genotypes [19,37]. One reason for the lack of an observed effect may be due to the limited ability of most previous studies to look at polymorphisms for several genes or SNPs jointly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…121). A large multiethnic study has indicated that CYP1B1 genotype is not associated with serum estrogen levels in premenopausal women (122). Another study investigating circulating estrogens in postmenopausal women has indicated that CYP1B1 genotype is not correlated with circulating estrogen levels (123), whereas another large study indicated that serum levels of estrogen are increased with the CYP1B1*1 genotype, whereas the CYP1B1*3 genotype correlates with an increased percentage of ER-positive tumors (124), thus confirming a previous observation (106).…”
Section: Contribution Of Polymorphisms To Increased/ Decreased Riskmentioning
confidence: 99%